HAK DAN KEWAJIBAN ORANG TUA TERHADAP ANAK BERDASARKAN PASAL 45 UNDANG UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Zulfikar, Teuku; Fathinuddin, Muhammad (CV. Era Digital Nusantara, 2023)
Humans are destined with the nature of zoon politicon, they always live in groups in a group called society. Living alone without other people somewhere is not human nature as a creature, even if there are people who live alone, it's a bedtime story and in the middle of the story they will definitely be met and get along with each other as an absolute necessity. It is human nature to live side by side with other humans and try to carry on offspring by means of marriage. Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the One Godhead. with the aim, among other things, to get offspring who will continue and replace the generation that gave birth to them. The purpose of this study was to find out how the rights and obligations of parents towards children based on Article 45 of Law Number 1 of 1974 concerning Marriage. Based on Article 45 and Article 46 of Law no. 1 of 1974, the obligation of parents to care for and educate their children until they marry and can stand alone. This also means that even if the child is married if, in fact, it cannot stand alone, it is still the obligation of parents to take care of their children, wives, and grandchildren. This is different from what is regulated in the Civil Code that the obligation does not only extend to adult children (aged 18 years) but until they are able to stand on their own even though the marital ties of their parents are broken. Children must respect their parents and obey their goodwill. If the child is an adult, he is obliged to take care of his parents and family in a straight line up according to his ability, if they need his help